2016
DOI: 10.1038/srep27043
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA Repair Capacity, Cell Death and Transcriptional Response after Irradiation between a Radiosensitive and a Radioresistant Cell Line

Abstract: Normal tissue toxicity after radiotherapy shows variability between patients, indicating inter-individual differences in radiosensitivity. Genetic variation probably contributes to these differences. The aim of the present study was to determine if two cell lines, one radiosensitive (RS) and another radioresistant (RR), showed differences in DNA repair capacity, cell viability, cell cycle progression and, in turn, if this response could be characterised by a differential gene expression profile at different po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 71 publications
3
35
0
Order By: Relevance
“…To exclude the possibility that genes in our core signature were predictors of a general response to genotoxic stress, we interrogated published datasets that used mild forms of DNA damage ([31]; GEO:GSE80207). Only one gene in our signature ( PLK3 ) was reported differentially expressed in a radiosensitive lymphoblast line 4 hr after exposure to 2 Gy ionizing radiation (false discovery rate [FDR] ≤ 0.05), a dose that causes damage without pervasive permanent cell-cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…To exclude the possibility that genes in our core signature were predictors of a general response to genotoxic stress, we interrogated published datasets that used mild forms of DNA damage ([31]; GEO:GSE80207). Only one gene in our signature ( PLK3 ) was reported differentially expressed in a radiosensitive lymphoblast line 4 hr after exposure to 2 Gy ionizing radiation (false discovery rate [FDR] ≤ 0.05), a dose that causes damage without pervasive permanent cell-cycle arrest.…”
Section: Resultsmentioning
confidence: 99%
“…The survival of DNA-damaged cancer cells is determined by whether cancer cells can repair damage to DNA (44,45). The current study revealed that the viability of Capan-1 cells was decreased and not in Panc-1 cells, and the difference was associated with a decrease of RAD51 expression.…”
Section: Discussionmentioning
confidence: 52%
“…The fate of DNA-damaged cancer cells by chemotherapy and radiotherapy is determined by whether DNA damage is repaired (44,45). Therefore, the activities of DNA repair enzymes have been demonstrated to be closely associated with cell death and cell cycle arrest (45).…”
Section: Pb Irradiation Decreases Rad51 Expression In Capan-1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies showed that ncRNAs can modulate programmed cell death after IR [147,148]. Apoptosis is an acclaimed indicator of cellular radiosensitivity and a prognostic factor of radiotherapy treatment outcome [149,150]. Apart from apoptosis, cell death after IR can also occur via necrosis and mitotic catastrophe.…”
Section: Ncrnas Regulating Ir-induced Apoptosismentioning
confidence: 99%